2021
DOI: 10.1016/j.jdin.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Burden of skin disease and associated socioeconomic status in Asia: A cross-sectional analysis from the Global Burden of Disease Study 1990-2017

Abstract: Introduction Skin diseases have a significant global impact on quality of life, mental health, and loss of income. The burden of dermatologic conditions and its relationship with socioeconomic status in Asia is currently not well understood. Methods We selected Global Burden of Disease Study datasets to analyze disability-adjusted life years (DALYs) in 50 Asian countries, including Central Asia, northern Asia, eastern Asia, western Asia, southeastern Asia, and southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 41 publications
0
44
0
2
Order By: Relevance
“…49 The Pooja study (2020) modality of PRP therapy in acne scars when monotherapy is used (single therapy) is not recommended because the results are unsatisfactory. 50 Ibrahim's study (2017) combined therapy in the treatment of acne scars showed satisfactory results when PRP was used in combination with other modalities such as microneedling and CO2 laser. 51 Faghihi study (2016) acne scar therapy using a combination of PRP with CO2 laser, gave insignificant results, a synergistic effect with uncomfortable side effects and took longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The Pooja study (2020) modality of PRP therapy in acne scars when monotherapy is used (single therapy) is not recommended because the results are unsatisfactory. 50 Ibrahim's study (2017) combined therapy in the treatment of acne scars showed satisfactory results when PRP was used in combination with other modalities such as microneedling and CO2 laser. 51 Faghihi study (2016) acne scar therapy using a combination of PRP with CO2 laser, gave insignificant results, a synergistic effect with uncomfortable side effects and took longer.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In 2010, East Asia, South Asia, and Western Europe were the regions with the highest prevalence of acne vulgaris in the world in the 15-19 year age group (men: 49%; women: 51%) almost the same. 7,8 The management of acne scars is carried out by several methods such as topical preparations, dermabrasion, laser, excision (punch and elevation), subcutaneous incision, chemical peeling, dermal graft, filler, and microneedling (automated and dermaroller). 1,2,[9][10][11] Grade assessment acne scar severity using the Goodman and Baron subjective method.…”
Section: Introductionsmentioning
confidence: 99%
“…According to research, dermatological illnesses account for 1.8 % of worldwide disease burden and are rated fourth among all diseases that impact humans. Skin illnesses impact at least one-third of the population at some point in their lives, and they affect people of all ages, from infants to the elderly, and from all cultures ( Urban et al, 2021 , Tizek et al, 2019 ). There is significant variation in the number of different dermatological diseases among various regional and socio-economical situations.…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variation in the number of different dermatological diseases among various regional and socio-economical situations. Skin cancers like melanoma, for example, are more common in high-income nations like Central Europe, North America, and Australia ( Urban et al, 2021 ). Even though skin problems are common throughout Asia, few research on skin diseases has been quantitatively reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation